Multi-class determination of intracellular and extracellular cyanotoxins in freshwater samples by ultra-high performance liquid chromatography coupled to high resolution mass spectrometry. (July 2021) - Romera-García, Encarnación; Helmus, Rick; Ballesteros-Gómez, Ana; Visser, Petra M.
Abstract: In the past decades, the intensity and duration of cyanobacterial blooms are increasing due to anthropogenic factors. These phenomena worry drinking water companies and water managers because cyanobacteria produce a diverse range of cyanotoxins, which can cause liver, digestive and neurological diseases. The main exposure routes for humans are the consumption of drinking water that has not been effectively treated and the recreational use of polluted waters. For risk assessment and to conduct studies on large-scale occurrence, the development of reliable but simple, sensitive and cost-effective analytical approaches able to cover a wide range of cyanotoxins is essential. Additionally, the determination of intracellular and extracellular toxins separately is advantageous for risk management. To the best of our knowledge, this is the first time that a method for the multi-class determination of cyanotoxins in fresh water, which is able to separately report intra- and extracellular toxins, meet the criteria of simplicity (not requiring multiple sample preparation procedures or time-consuming steps) and it is based on highly specific high resolution mass spectrometry (potential for wide screening and retrospective analysis). Matrix effects, trueness and precision met general validation criteria for a group of nine cyanotoxins, including anatoxins, cylindrospermopsin and microcystins. Considering a 50 mL sample, the method quantification limits were within the range of 8–45 ng L −1 and 25–129 ng L −1 for intra- and extracellular cyanotoxins, respectively. Anatoxin-a, cylindrospermopsin and some microcystins were found in three out of four Dutch lakes included in the study, at concentrations up to 52 μg L −1 . Highlights: The method determines intra- and extracellular multi-class cyanotoxins separately. Sample preparation is simple and cost-effective and method met validation criteria. The method is based on highly specific HRMS (potential for retrospective analysis). ANA, CYL and some MCs were found in Dutch lakes. The MCs concentration in a Dutch lake was above the guideline within the Netherlands.